Thermal conductivity, thermal diffusivity, and thermal capacity of some Nigerian soils - Ghuman, B.S.; Lal, R. (Ovid Technologies, 1985)
Thermal conductivity increased with increasing soil water content. Clayey soils had lower thermal conductivity than sandy soils at all water levels studied. Thermal conductivity ranged from 0.37 to 1.42 for sandy loam, from 0.37 to 1.90 for loam, from 0.38 to 1.71 for sandy clay loam, and from 0.39 to 0.41 mcal/s [middle dot] cm [degrees]C for clay soils at water contents from 0.02 to 0.16 cm3 cm-3. Thermal conductivity differences among soils were smaller at lower soil water contents than at higher water contents. Thermal conductivity did not continuously increase with water content for the washed sand. Soil containing gravel had lower thermal conductivity than gravel-free soil. Thermal conductivity for a gravelly soil measured in situ was appreciably lower than that of the sieved and homogeneous laboratory soil columns. Thermal diffusivity of sandy or loamy soils increased with water content to the peak and then decreased with further increase in water content. Soils of fine texture, however, did not exhibit a distinct thermal diffusivity peak. Volumetric heat capacity calculated from measured values of thermal conductivity and diffusivity agreed closely with those estimated from volume fractions of soil components (by the de Vries equation) for coarse- to medium-textured soils, but not for fine-textured soils. At air-dry wetness, clayey soils generally had higher thermal capacity than sandy soils.